2018
DOI: 10.1038/s41598-018-29887-5
|View full text |Cite
|
Sign up to set email alerts
|

First-principles and Molecular Dynamics simulation studies of functionalization of Au32 golden fullerene with amino acids

Abstract: With the growing potential applications of nanoparticles in biomedicine especially the increasing concerns of nanotoxicity of gold nanoparticles, the interaction between protein and nanoparticles is proving to be of fundamental interest for bio-functionalization of materials. The interaction of glycine (Gly) amino acid with Au32 fullerene was first investigated with B3LYP-D3/TZVP model. Several forms of glycine were selected to better understand the trends in binding nature of glycine interacting with the nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Nazmutdinov et al used the B3PW91 functional and showed CYS binding to planar Au 12 cluster through thiol and carboxyl. Ganji et al obtained at the B3LYP-D3/TZVP level CYS with Au 32 fullerene mediated by sulfur, like Pelayo et al with PBE functional and Pérez et al using PBE functional to study Au 55 cluster. Carr et al found that multiple CYSs interact with Au 55 forming a double layer, where the internal layer is chemisorbed on the surface through the thiol, while the external layer interacts with the carboxyl and amino groups through hydrogen bonds .…”
Section: Resultsmentioning
confidence: 99%
“…Nazmutdinov et al used the B3PW91 functional and showed CYS binding to planar Au 12 cluster through thiol and carboxyl. Ganji et al obtained at the B3LYP-D3/TZVP level CYS with Au 32 fullerene mediated by sulfur, like Pelayo et al with PBE functional and Pérez et al using PBE functional to study Au 55 cluster. Carr et al found that multiple CYSs interact with Au 55 forming a double layer, where the internal layer is chemisorbed on the surface through the thiol, while the external layer interacts with the carboxyl and amino groups through hydrogen bonds .…”
Section: Resultsmentioning
confidence: 99%
“…Au 32 , as shown in Fig. S1 (ESI†), is an icosahedral fullerene-like nanostructure, first computationally predicted to be stable by Johansson et al 33 Since then, several works have been done with Au 32 as the starting model to study the interaction between GNP with amino acids 20 and small molecules (CO, H 2 , O 2 ). 39,40 To assess the reactivity of Au 32 , the condensed Fukui function has been computed using an analytical approach, as implemented in deMon2k.…”
Section: Methodsmentioning
confidence: 99%
“…Several computational studies investigate the interaction at the interface of nanoparticles with various molecules, such as oxygen, carbon monoxide, amino acids, etc. 18–23 However, these efforts have faced several challenges that include the complexity of nanoparticles in terms of size and shape, which result in different reactivity sites.…”
Section: Introductionmentioning
confidence: 99%
“…We also check the influence of the dispersion interactions on structural optimization. 28–31 We take two configurations (with and without a strain) as examples, and reoptimize them by employing both Grimme DFT-D2 and Grimme DFT-D3 methods. For our negative-Poisson's-ratio systems, under a longitudinal compressive/tensile strain, the lateral width is the most important geometric parameter, and we find that the absolute values of variation ratios of the widths are all smaller than 1.3%, and most of them are smaller than 0.6%, compared with that of a conventional DFT method without dispersion correction (see the ESI†).…”
Section: Methodsmentioning
confidence: 99%